(untitled) (Al-Academy, 2015)
This research includes interested in studying art contemporary, by studying the experiences of sculpture for the formation of post-modernism, assuming the existence of trends in public art can be classified, in spite of the multiplicity of styles and methods of work since the second half of the twentieth century to the present day, and this shenanigans knowledge on how to the Technical that is the art is not restricted, It is art refuses laws and fixed values and traditional styles, and always aspires to diversity and innovation.Search contains three chapters and an introduction containing information about the research problem and the importance of research and the goal of the research, the goal of research is: Detection of artistic trends in the formation of post-modernism, as well as the limits of search time between 1950 2010 AD, and the limits of search spatial are in Europe and the United States, due to the fact that Search one of the research-based analytical cash to draw conclusions from the study of the experiences of general, the survey method was used in the study of descriptive research sample, according to the models included in the chapters : first and second.The first chapter provided information on techniques to show the formation of post-modernism, in order to identify the modes of these techniques and methods of formation. While the second chapter included the modalities of supply in the formation of post-modernism, which is an important aspect of this trend for the disclosure of those methods and exit information and data derived it .The third chapter is devoted to the search results, by showing that there are five key trends for the formation of post-modernism:1)body art , includes the arts which focused on the representation of the human body, such as: the realistic Art Pop art and performance art2) environmental art , includes arts which focused on taking the natural environment the subject of works of art , with or without human intervention .3) Kinetic Art : Includes Arts which focused on the element of movement in the sculptural works .4) materials of non-traditional art : the arts that includes premium materials used in artwork: light, sound, water, and chemical industrial materials, electronic screen.5 ) Constructivist art: Includes arts, which focused on the establishment of artwork through traditional materials: Diversified Metals and stone and wood, appeared in abstract art and assembly art , or through the ready-made materials through installed or displayed